Averrhoa bilimbi leaves-derived oxygen doped 3D-linked hierarchical porous carbon as high-quality electrode material for symmetric supercapacitor. (15th August 2022) - Taer, Erman; Apriwandi, Apriwandi; Nursyafni, Nursyafni; Taslim, Rika
Abstract: This successfully performed a facile one-way KOH impregnation strategy, to hierarchically prepare interconnected porous carbon and self-oxygen doped from Averrhoa bilimbi leaves waste, as binder-free electrode material (PCBLs) for high-quality symmetrical supercapacitor. 3D porous structure and surface area PCBLs-derived controlled by different KOH concentrated solution. KOH infiltrated into precursor as act activation agent to completely removed inorganic impurities, result high carbon content of 85.54–87.22% with oxygen functional group of 10.61–14.71%. The precursor impregnated at 0.5 mol/L possessed excellent micropores 87.69%, adjusting mesopores and appropriate amounts of oxygen doped of 14.71%. As a result, it performed high performance of symmetrical supercapacitor. Furthermore, the electrochemical performance was evaluated within a two-electrode system using a binder-free solid coin design in different aqueous electrolytes of 1 M H2 SO4, NaOH, and Na2 SO4, respectively. This indicated that the symmetric supercapacitor-based PCBL-5 had a high specific capacitance of 293 F g −1 in 1 M H2 SO4 aqueous electrolyte at a current density of 1.0 A g −1 . It also showed impressive energy densities of 26.54, 21.85, and 16.12 Wh kg −1 in 1 M H2 SO4, NaOH, and Na2 SO4, at an optimum power density of 178.44 W kg −1 . The observed desirable excellent material and electrochemical behaviors of the new source hierarchical porous carbon derived from Averrhoa bilimbi leaves waste would be a competitive candidate as electrode material in the development of high-quality supercapacitor devices. Graphical abstract: Unlabelled Image Highlights: A facile one-way KOH impregnation strategy obtains high-quality carbon electrode. Averrhoa bilimbi leaves-derived carbon contains enrich self-oxygen doping. PCBLs has possesses 3D hierarchical porous carbon with abundant micropores. The symmetric supercapacitor has high specific capacitance 293 F g −1 at 1 A g −1 . The energy density is 26.5 Wh kg −1 at coulombic efficiency of 70.5%.